Situation Report: Czechoslovakia, 3 November 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Official References to the Events of 1968 The Convertibility of the Koruna Czechoslovakia's Audio-Visual Industry Problems with Army Recruits / by Jan Obrman The Congresses of the Socialist Youth Union / by Jan Obrman The Vatican's Esteem for Three Figures of Czech Religious History / by Antonin Kratochvil Stredni Evropa: A Conservative Czech Samizdat Journal